Multi-level kinetic model explaining diverse roles of isozymes in prokaryotes - Jablonsky, Jiri; Schwarz, Doreen; Hagemann, Martin (PLoS One, 2014)
Current standard methods for kinetic and genomic modeling cannot provide deep insight into metabolic regulation. Here, we developed and evaluated a multi-scale kinetic modeling approach applicable to any prokaryote. Specifically, we highlight the primary metabolism of the cyanobacterium Synechococcus elongatus PCC 7942. The model bridges metabolic data sets from cells grown at different CO2 conditions by integrating transcriptomic data and isozymes. Identification of the regulatory roles of isozymes allowed the calculation and explanation of the absolute metabolic concentration of 3-phosphoglycerate. To demonstrate that this method can characterize any isozyme, we determined the function of two glycolytic glyceraldehyde-3-phosphate dehydrogenases: one co-regulates high concentrations of the 3-phosphoglycerate, the other shifts the bifurcation point in hexose regulation, and both improve biomass production. Moreover, the regulatory roles of multiple phosphoglycolate phosphatases were defined for varying (non-steady) CO2 conditions, suggesting their protective role against toxic photorespiratory intermediates.
Keywords: oxidace-redukce; glyceraldehyd-3-fosfátdehydrogenasy; Oxidation-Reduction; oxid uhličitý; Synechococcus; Bacterial Proteins; Kinetics; Isoenzymes; Adenosine Triphosphate; homeostáza; Glyceraldehyde-3-Phosphate Dehydrogenases; NADP; Homeostasis; izoenzymy; adenosintrifosfát; kinetika; bakteriální proteiny; Carbon Dioxide